Revitalizing Pakistan’s Fisheries : Options for Sustainable Development - World Bank Group (World Bank, Washington, DC, 2018)
The report is the result of detailed research and consultation, which included review of literature, original analysis of fisheries data, and extensive meetings with people from the Federal Government, Provincial Governments, the private sector, and non-government and international organizations. Consultations were roughly evenly divided across capture fisheries, culture fisheries, and cross-cutting issues. The findings are organized in four remaining sections: part two provides an overview of the current state of fisheries in Pakistan. Information on fisheries' contribution to the economy, production trends, and fishing practices for marine, inland, and aquaculture is presented. Part two also provides an overview of the existing fisheries governance arrangements including current policy and legal framework and institutional arrangements. Part three provides an analysis of the potential benefits that could be realized through a revitalization of Pakistan’s fishery sector. Part four gives an analysis of the challenges to realizing these benefits. Part five describes specific activities necessary to overcome the challenges identified in part four. It provides recommendations within five themes: (1) creating an enabling environment for growth, (2) managing marine capture fisheries for long-term sustainability, (3) ensuring sustainable inland capture fisheries, (4) supporting the development of an environmentally sensitive aquaculture industry, and (5) optimizing the benefits of a productive fisheries sector for social goals.